1998
DOI: 10.1111/j.1749-6632.1998.tb09725.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Neurobehavioral and Neuroanatomic Correlates of Prenatal Cocaine Exposure: Problems of Dose and Confounding

Abstract: Complex methodologic challenges face researchers studying the effects of prenatal cocaine exposure on infant outcome. These include unavoidable imprecision in ascertaining the gestational timing and dose of cocaine to which the fetus was exposed and difficulties in identifying and quantifying the confounding, mediating, and moderating variables. Review of research on neonatal behavioral and cranial ultrasound findings following in utero cocaine exposure is used to illustrate these issues. We conclude that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…30 Maternal self-report scales are low in cost, readily available, generally well standardized, and easily administered. 31 In the present study, more than one-third of the mothers admitted continued cocaine and/or heroin use. Although the validity of maternal self-report has been questioned, 30 the mothers in the present study may have felt more comfortable admitting ongoing drug use because of the continuity of the research team, and because all the mothers were admitted drug users.…”
Section: Discussionmentioning
confidence: 50%
“…30 Maternal self-report scales are low in cost, readily available, generally well standardized, and easily administered. 31 In the present study, more than one-third of the mothers admitted continued cocaine and/or heroin use. Although the validity of maternal self-report has been questioned, 30 the mothers in the present study may have felt more comfortable admitting ongoing drug use because of the continuity of the research team, and because all the mothers were admitted drug users.…”
Section: Discussionmentioning
confidence: 50%
“…Methodological differences between studies can also influence outcomes. These may include subject characteristics, demographics, and enrollment criteria; the specific covariates controlled in the analyses; the unknown purity and varying routes of administration and timing of use of the illegal drug during pregnancy; as well as the specific developmental outcomes tested [26], [72]. When evaluating potential IUCE effects, other factors such as, gender, IQ, and maternal education which influence cognitive outcomes of children in general must be addressed either by subject selection or statistical control [7], [56], [27], [51].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from prior analyses in this cohort indicated that IUCE defined this way was significantly related in a linear dose-dependent manner to lower birth weight z -scores adjusted for gestational age and sex [45], less optimal patterns of newborn neurobehavior [136], and neonatal ultrasound findings [46]. This ordinal IUCE classification of the sample (unexposed, lighter exposed, heavier exposed), which was established at birth, was used as the primary predictor of NEPSY outcomes in the current analysis.…”
Section: Methodsmentioning
confidence: 99%